2021
DOI: 10.1542/peds.2020-001073
|View full text |Cite
|
Sign up to set email alerts
|

Five-Phase Replication of Behavioral Health Integration in Pediatric Primary Care

Abstract: BACKGROUND AND OBJECTIVES Because of severe and protracted shortages of pediatric behavioral health (BH) specialists, collaboration between pediatric primary care practitioners (PCPs) and BH specialists has the potential to increase access to BH services by expanding the BH workforce. In a previous study, we demonstrated that phase 1 of a behavioral health integration program (BHIP) enrolling 13 independently owned, community-based pediatric practices was associated with increased access to B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Behavioral health screening has been shown to increase in integrated behavioral health care settings. Walter et al (2021) showed that when behavioral health integration was implemented in primary care clinics, universal behavioral health screening increased from 55.6% to 73.9% ( p < .001). In a systematic review of pediatric integrated care models, all studies reviewed utilized behavioral health screening measures in their integrated model (Burkhart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral health screening has been shown to increase in integrated behavioral health care settings. Walter et al (2021) showed that when behavioral health integration was implemented in primary care clinics, universal behavioral health screening increased from 55.6% to 73.9% ( p < .001). In a systematic review of pediatric integrated care models, all studies reviewed utilized behavioral health screening measures in their integrated model (Burkhart et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Stepped Care Framework. In the stepped care model (example in Figure 3 135 ), the intensity of treatment is determined by the severity of the clinical presentation as assessed through standardized screening tools and focused symptom rating scales, and through focused clinical interview. For subclinical symptom presentations (concerning but not problematic), a range of preventive interventions can be used by the PCC and/or CM/BHC, including healthy lifestyle guidance (eg, nutrition, exercise, sleep, stress reduction) as the foundation for MH and wellness, and guided selfmanagement for patients and families who wish to learn and practice MH skills on their own with PCC/CM/BHC guidance and follow-up.…”
Section: Coordinated Clinical Service Modelsmentioning
confidence: 99%
“…A meta-analysis of more than 13,000 patients enrolled in 31 randomized controlled trials of pediatric collaborative care 33 demonstrated modestly superior clinical outcomes for collaborative care vs usual care (overall effect size: d ¼ 0.32, p < .001). When triadic models were examined separately from other models, the effect size compared to usual care Note: From: Walter HJ, Vernacchio L, Correa ET, et al 135 was considerably larger (d ¼ 0.63, p ¼ .001). Other subgroup analyses demonstrated that effects were larger for treatment (d ¼ 0.42, p < .001) than for prevention studies (d ¼ 0.07, p ¼ .49), and for MH treatment (d ¼ 0.51, p < .001) than for substance abuse treatment studies (d ¼ 0.17, p ¼ .35).…”
Section: Coordinated Clinical Service Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our education component diminished the costs of new curriculum development by adapting a previously tested, AAP competency-focused curriculum that was delivered with favorable outcomes to a large pediatric practice network in Massachusetts. [31][32][33] Our consultation component reduced the costs of on-demand CPAP-like consultation by utilizing local psychiatry resources that offered a limited schedule of consultation availability. Our care coordination component streamlined specialty BH referral by standardizing referral pathways to local psychotherapy and psychopharmacology resources, and by creating a resource directory for other BH services.…”
Section: Introductionmentioning
confidence: 99%